SINERGI DIGITAL-INTERDISIPLINER: PENGARUH PEMBELAJARAN STEAM BERBASIS APLIKASI GEOGEBRA TERHADAP REPRESENTASI GEOMETRI - Muhammad Arif Juliantoro; Siti Nur Azizah (Program Studi Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2026)
This study aims to determine the effect of STEAM learning based on the GeoGebra application on students’ geometric representation competence in three-dimensional geometry material. This research used a quantitative approach with a quasi-experimental design. The sample consisted of two eighth-grade classes at SMP Plus Darussalam Blokagung Banyuwangi. Data were collected through pretest, posttest, documentation, and assessment rubrics. The data analysis used normality test, homogeneity test, and Independent Sample t-Test using SPSS. The results showed that STEAM learning based on GeoGebra significantly improved students’ geometric representation competence. This learning model also enhanced students’ visualization skills, creativity, and active participation in mathematics learning.